Analisis Lingkungan Kerja terhadap Turnover Intentions pada Karyawan PT. Spesial Gold - Rafa Fitria; Lingga Yuliana (Master Manajemen, 2025)
This study analyzes the influence of the work environment on the turnover rate at PT Spesial Gold, with the method used in this study is a qualitative approach method. The sample collection technique uses purposive sampling where respondents are determined with the criteria of being employees who work at PT. Spesial Gold with customer service or sales positions. The results of interviews with respondents show that high workloads and ineffective communication are the main factors causing turnover. Poor relationships between superiors and subordinates, as well as inadequate work facilities, also contribute to employee dissatisfaction. Employees often show a desire to leave after one to two years of work, because they feel there is no career development. An uncomfortable work environment can cause stress and feelings of being unappreciated, encouraging employees to look for other opportunities. Recommendations to reduce turnover include improving internal communication, training for superiors, adjusting workloads, and providing employee welfare programs. This study emphasizes the importance of the role of management in creating a conducive work atmosphere.